2021
DOI: 10.1002/int.22471
|View full text |Cite
|
Sign up to set email alerts
|

License plate recognition using neural architecture search for edge devices

Abstract: The mutually beneficial blend of artificial intelligence with internet of things has been enabling many industries to develop smart information processing solutions. The implementation of technology enhanced industrial intelligence systems is challenging with the environmental conditions, resource constraints and safety concerns. With the era of smart homes and cities, domains like automated license plate recognition (ALPR) are exploring automate tasks such as traffic management and fraud detection. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Edge computing supports solves this issue by merely increasing the computational capabilities of the edge devices, thus reducing the communication cost and the application latency. Moreover, it has become possible to due to the increase in computational performance in edge devices without significantly compromising energy efficiency [57].…”
Section: Alpr Using Edge Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Edge computing supports solves this issue by merely increasing the computational capabilities of the edge devices, thus reducing the communication cost and the application latency. Moreover, it has become possible to due to the increase in computational performance in edge devices without significantly compromising energy efficiency [57].…”
Section: Alpr Using Edge Devicesmentioning
confidence: 99%
“…In our previous study [57], we have discussed the architecture of the Lite LP-Net models in detail. As the next phase, this paper mainly describes the hardware circuit configurations from the deployment point of view, synthetic data generation process, stochastic super-network implementation and the bi-level optimization in Section 3, as the scientific contribution.…”
Section: Alpr Using Edge Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method has been to use computer vision techniques to detect licence plate numbers. There are many challenges [9] to detecting vehicle licence plates covertly in remote jungle areas, such as limited visibility and lighting [10], limited connectivity, limited access to computation and energy sources [11], exposure to harsh jungle environments (e.g. humidity, water etc.)…”
Section: Vehicle Tracking Using Rfid/ble/vision Technologymentioning
confidence: 99%
“…1 This task aims to retrieve all the images of query vehicles in a large gallery set, where images are usually captured from nonoverlapping cameras under various viewpoints. Some previous works [2][3][4] demonstrated that the local-specific features, such as license plate and custom logos, can provide recognizable information for identifying two vehicles. However, due to the influence of illumination, occlusion, or cross-view in the real environment, subtle local-specific features might be unavailable.…”
Section: Introductionmentioning
confidence: 99%